Synergy of Science Literacy and Student Sustainability Literacy in Biology Learning Towards the Sustainable Development Goals Agenda - Nukhbatul Bidayati Haka; Anggun Fransiska; Meita Dwi Solviana; Hardiyansyah Masya; Tengku Idris (Pustaka Digital Indonesia, 2026)
The urgency of this research is to strengthen the synergy between science literacy and students' sustainability literacy in biology learning to support the achievement of the Sustainable Development Goals (SDGs) .The Sustainable Development Goals (SDGs) agenda requires biology learning to be oriented not only towards mastering concepts but also towards fostering ecological awareness, sustainability mindsets, and student action competencies to address the 21st-century environmental crisis. The low achievement in science literacy among Indonesian students in the Programme for International Student Assessment, coupled with biology learning that is predominantly theoretical and memorized, underscores the importance of strengthening the synergy between science literacy and sustainability literacy. The research aims to analyze the correlation between science literacy and sustainability literacy among grade X students in ecosystem materials, as a basis for developing biology learning that supports the SDGs agenda. The research sample comprised 276 students selected through purposive sampling from SN4, SN10, SN14, and SN16. The research instrument consisted of 20 multiple-choice science literacy tests, 18 statements of science identity questionnaires, and 18 statements of literacy questionnaires. Data were analyzed using SPSS for normality, homogeneity, linearity, moment product correlation, simple linear regression, and the coefficient of determination. The results of the study show variation in achievement across schools. SN10 obtained the highest average scores in science literacy (85.46%) and sustainability literacy (92.36%). Meanwhile, SN16 had the lowest average sustainability literacy score at 56%. Knowledge displacement in sustainability literacy reached the highest level across schools, while the dimensions of skills and mindset were lower. The correlation results showed a positive and significant relationship between science literacy and sustainability literacy, with a very strong correlation in SN14 of r= 0.909 with R2=82.7%, and SN10 of r= 0.894 with R2=79.9%. These findings confirm that science literacy is an important foundation for building students' sustainability literacy, so biology learning on ecosystem materials needs to be integrated to support the achievement of the Sustainable Development Goals agenda.